KEONG HAMA Pomacea DI INDONESIA: KARAKTER MORFOLOGI DAN SEBARANNYA(MOLLUSCA, GASTROPODA: AMPULLARIIDAE) - Isnaningsih, Nur Rohmatin; Marwoto, Ristiyanti M (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The golden apple snail Pomacea is an invasive species not only in Indonesia but mostly in Southeast Asia. The snail caused serious damaged on more than thousands hectares of rice-fields. The study was based on the specimens deposited at the Museum Zoologicum Bogoriense (MZB)aimed to evaluate the occurrence of Pomacea and its distribution in Indonesia.Based on the shell characters there are four species recognized which are P. canaliculata, P.insularum, P. scalaris, P.paludosa that found from many places, and noted that P. canaliculata has wider distribution from Sumatra to Papua. The description of each species was presented at this paper as well as the map of the occurrence of Pomacea in Indonesia.